2020
DOI: 10.1111/ene.14492
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus due to marked enlargement of spinal roots in a patient with chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Background: Hydrocephalus or papilledema has rarely been reported in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods: We report a 65-year-old woman with a 12-year history of CIDP presenting with progressive dementia, hallucination and deterioration of gait. Results: Neurological examination revealed cognitive impairment, symmetric proximal and distal weakness with areflexia and muscle atrophy in the distal four limbs. The cerebrospinal fluid examination showed marked ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mental status decline in CIDP patients is usually considered ancillary to the primary disease with no causal link established between the two [ 5 ]. Newer investigations into cognition in CIDP have demonstrated various mild neurofunctional impairments, specifically with information processing speed, flexibility, and verbal processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental status decline in CIDP patients is usually considered ancillary to the primary disease with no causal link established between the two [ 5 ]. Newer investigations into cognition in CIDP have demonstrated various mild neurofunctional impairments, specifically with information processing speed, flexibility, and verbal processing.…”
Section: Discussionmentioning
confidence: 99%
“…There is an incredible paucity of information regarding CIDP and cognitive decline. The few reports are largely anecdotal and unsupportive of a direct causal link between CIDP and cognitive impairment [ 5 ]. Aside from neurological manifestations, new studies have delved into a potential link between gastrointestinal dysfunction and CIDP [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,8 Hydrocephalus, meanwhile, is rarely observed in patients with CIDP and to our knowledge has only been reported in 14 prior cases. 9 The mechanism is unknown, although it has been suggested that hypertrophied spinal nerve roots can result in obstructed CSF flow. 9 Protein-related blockage of the arachnoid villi is another possibility and may have played a role here.…”
Section: Discussionmentioning
confidence: 99%
“…9 The mechanism is unknown, although it has been suggested that hypertrophied spinal nerve roots can result in obstructed CSF flow. 9 Protein-related blockage of the arachnoid villi is another possibility and may have played a role here. 10 Elevated CSF protein is of course not unique to CIDP and can be seen in both acquired and hereditary demyelinating polyneuropathies.…”
Section: Discussionmentioning
confidence: 99%